ETHIOLOGY OF COMMUNITY ACQUIRED URDVARY INFECTIONS. A NINE YEAR STUDY - N Galué; M Ginestre; A Martínez; S Romero; G Rincón; B Harris (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2000)
BACKGROUND: The frequency of uropathogens depends on the geographic location, age, sex and procedence of the patients (inpatients and outpatients). In order to determine prevalence of pathogens in the urinary tract, a retrospective analysis was performed of the urine cultures processed during the last nine years. METHODS: 5223 urine cutures were studied from patients attending the LUZ Clinical Laboratory between years 1990-1999. Bacterial cuantification in midstream urine specimens was made applying the calibrated loop technique. Bacterial identification was made by means of routine laboratory procedures. RESULTS: Among the 5223 urine cultures processed, 1153 (22,38% ) presented significant pathogens, 84,00% belonging to female patient urine cultures. Bacteriuria for more than one microorganism was 4,00%. The most frequently isolated microorganism was Escherichia coli (63,00%), followed by Gardnerella vaginalis (8,32%). Even though Gardnerella vaginalis occupies second place, the isolation of this microorganism has decreased significantly, and only one yearly isolation was made during the last two years of the study. Other microorganisms present were: Klebsiella pneumoniae (7,29%), Proteus mirabilis (6,33%), other Enterobacteriaceae (5,00%), Psueudomonas aeruginosa and other Gram-negative glucose non-fermenting rods (4,00%), Streptococcus Group B and other Streptococcus (2,00%), Enterococcus (2,00% ), Staphylococcus aureas (1,00%), Aeromonas sp. (0,30%), Haemophilus influenzae (0,10%) and Candida sp. (1,00%). CONCLUSIONS: Escherichia coli continues to be the most frequently isolated pathogen. Regarding Gardnerella vaginalis, further studies should be made to understand the role of this organism in bacteriuria and its real incidence in urinary infections.